2000
DOI: 10.1164/ajrccm.161.3.9802013
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus albidus-induced Summer-type Hypersensitivity Pneumonitis

Abstract: We studied summer-type hypersensitivity pneumonitis believed to be induced by Cryptococcus albidus in the home environments of the patients. All patients had antibodies that were reactive to Cryptococcus neoformans and Trichosporon cutaneum in sera and bronchoalveolar lavage (BAL) fluids. Cryptococcus albidus strains were isolated from 62.5% of the patient home environments. Trichosporon cutaneum was found in none of the patient homes. To study local antibody production in the lung, we cultured BAL cells to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Chest radiograph findings included localized opacities, disseminated nodular infiltration mimicking miliary patterns, cavity lesions, hilar node enlargement, pleural fluid and diffuse bilateral opacification with or without a pattern similar to that seen in ARDS. Notable, the investigators of one report suggested that C. albidus may be an etiologic agent of summer-type hypersensitivity pneumonitis [47].…”
Section: Pulmonary Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest radiograph findings included localized opacities, disseminated nodular infiltration mimicking miliary patterns, cavity lesions, hilar node enlargement, pleural fluid and diffuse bilateral opacification with or without a pattern similar to that seen in ARDS. Notable, the investigators of one report suggested that C. albidus may be an etiologic agent of summer-type hypersensitivity pneumonitis [47].…”
Section: Pulmonary Infectionmentioning
confidence: 99%
“…The mean duration of treatment for meningitis was 60 days [22], with 17 days (ranged 14-20 days) for fungemia [28,29] and 90 days for empyema [47]. One patient developed leukopenia and anemia as side effects of conventional amphotericin B (1 mg/kg/day) and therapy was switched to itraconazole [52].…”
Section: Cryptococcus Albidusmentioning
confidence: 99%
“…In contrast, hypersensitivity pneumonitis from routine domestic exposures has been well described in other countries. The endemic Japanese summer-type hypersensitivity pneumonitis has been commonly associated with domestic exposure to Trichosporon cutaneum or Cryptococcus albidus (7), fungi that grow in rotting structural wood or wet tatami mats in residences (8). This kind of hypersensitivity pneumonitis has also been reported in South African residences (9).…”
Section: Discussionmentioning
confidence: 99%
“…C albidus ha estado implicada en infecciones respiratorias severas, del sistema nervioso central y en fungemias. [29][30][31] Es posible que el hallazgo de esta levadura sea comúnmente subestimado y que esté jugando un papel patógeno importante, particularmente en pacientes inmunosuprimidos. como el que hemos presentado, constituyen el paso fundamental para detectar los problemas de salud de nuestra población.…”
Section: Hongos Contaminantes Sin Significación Patogénica Aislados Dunclassified